Financing Restructuring Effort to Handle Problem Financing During in the Pandemic Time Covid-19 at PT. Bank Sumut Syariah Kantor Cabang Pematang Siantar - Fazha Alfa Said Syah (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
The covid-19 pandemic has a significant impact on all aspects of human life, especially in the economic sector. In the banking sector, the existence of lockdown rules has preventedseveral business sectors from running, as a result it is difficult for business sectors that have loans from bank to repay loans. This study aims to fine out how toimplement financing restructuring during Covid-19 pandemic at PT. Bank Sumut Syariah Kantor Cabang Pematang Siantar. This Type of research is a qualitative research based on a descriptive approach. Techniques in data collection based on observation, interview and documentation. The analysis result shows taht the implementation of the financing restructuring at  PT. Bank Sumut Syariah Kantor Cabang Pematang Siantar)